2008
DOI: 10.1177/1077559507312962
|View full text |Cite
|
Sign up to set email alerts
|

How Do High-Risk Youth Use the Internet? Characteristics and Implications for Prevention

Abstract: Using data from the Second Youth Internet Safety Survey, a nationally representative telephone survey of 1,500 youth Internet users (ages 10 to 17), this study explores differences in Internet use characteristics between high risk youth and other Internet users. Those youth who engaged in aggressive behavior online and those who used the Internet on a cell phone were about twice as likely to be classified as high risk (having experienced high parent conflict or child maltreatment) as compared to other Internet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 23 publications
3
69
0
2
Order By: Relevance
“…Valkenburg and Peter (2009) propose a 'rich get richer' hypothesis, namely that those with already wide networks gain disproportionally by extending these online, building on earlier theories of knowledge gaps, technology diffusion and the digital divide. Others are investigating the converse, namely that those already disadvantaged offline (whether lonely or dissatisfied or with psychological problems) are becoming newly vulnerable online also (Mitchell, Finkelhor, & Wolak, 2007;Wells & Mitchell, 2008). These parallel research literatures are thus exploring the emerging opportunities -for education, expression and civic participation (Kalmus, et al, 2009;Livingstone & Helsper, 2010;Valkenburg & Peter, 2009) and the emerging risks -for cyberbullying, sexual harassment and stranger contact (Brandtzaeg, Staksrud, Hagen, & Wold, 2009;Erdur-Baker, 2010) of SNS use.…”
Section: Does the Use Of Social Networking Sites Increase Children's mentioning
confidence: 99%
See 1 more Smart Citation
“…Valkenburg and Peter (2009) propose a 'rich get richer' hypothesis, namely that those with already wide networks gain disproportionally by extending these online, building on earlier theories of knowledge gaps, technology diffusion and the digital divide. Others are investigating the converse, namely that those already disadvantaged offline (whether lonely or dissatisfied or with psychological problems) are becoming newly vulnerable online also (Mitchell, Finkelhor, & Wolak, 2007;Wells & Mitchell, 2008). These parallel research literatures are thus exploring the emerging opportunities -for education, expression and civic participation (Kalmus, et al, 2009;Livingstone & Helsper, 2010;Valkenburg & Peter, 2009) and the emerging risks -for cyberbullying, sexual harassment and stranger contact (Brandtzaeg, Staksrud, Hagen, & Wold, 2009;Erdur-Baker, 2010) of SNS use.…”
Section: Does the Use Of Social Networking Sites Increase Children's mentioning
confidence: 99%
“…When cyberbullying was encountered in social networking sites it tended to be sexual and it occurred in communities in which the users are anonymous, which is not the case on many SNS. A study of high risk users found little association with particular platforms of Internet use, although high risk youth are more likely to talk to new people they meet online (Wells & Mitchell, 2008), and this facility is enabled by SNS; the EU Kids Online survey found that 39% of 11-16 year olds are in contact with "friends of friends" online that they do not know face-to-face, and 25% contact people online who have no connection to their offline lives (Livingstone, Haddon, Görzig, & Ólafsson, 2011).…”
Section: From Computer-mediated Communication To Social Networkingmentioning
confidence: 99%
“…Of those who met the youngsters from Cluj Napoca 12.4% said nothing of their actual intentions, and only 7.4% made an indecent offer. Several studies confirm that youngsters are brought together online by personal interest, shared hobbies and age-related characteristics (see for example Wells & Mitchell, 2008;Dombrowski et al, 2007).…”
Section: Outcome Of Meeting Persons Encountered Onlinementioning
confidence: 90%
“…Research using the Second Youth Internet Safety Survey showed that "high risk" youth (those exposed to severe abuse or parent conflict) were more likely to talk with people they met online, engage in online aggression, and receive aggressive sexual solicitation [61]. A longitudinal study with a similar sample showed that adolescents exposed to early family conflict prefer online communication over in-person contact, seek support from others online when feeling depressed, yet form weak relationships with people met online [62••].…”
Section: Internet Technology Use and Its Impact On Vulnerable Youthmentioning
confidence: 99%